The gift of dyslexia : why some of the smartest people can't read-- and how they can learn - Davis, Ronald D. (Ronald Dell), 1942-; Braun, Eldon M., 1943- (New York, N.Y. : Penguin Group, 2010)
This book outlines a unique and revolutionary program with a phenomenally high success rate in helping dyslexics learn to read and to overcome other difficulties associated with it. This new edition is expanded to include new teaching techniques and revised throughout with up-to-date information on research, studies, and contacts.
"A Perigee book."
"The world's most widely used method of correcting Dyslexia and other learning problems"--Cover.
Includes bibliographical references (p. 259-263) and index.
Keywords: Dyslexia; Dyslexic children -- Education